KOMUNIKASI TRANSAKSIONAL PEMBIMBING KEMASYARAKATAN DALAM PROSES BIMBINGAN KONSELING PEMASYARAKATAN TERHADAP KLIEN ANAK DI BAPAS KELAS II BENGKULU - Rupian Joyo; Mas Agus Firmansyah; Dhanurseto Hadiprashada (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The purpose of this research is to determine the transactional communication of pembimbing kemasyarakatan with child clients in the guidance counselling process at the Class II Bengkulu Bapas. This research approach uses qualitative methods. Informants were selected by pembimbing kemasyarakatan and child clients and determined using purposeful techniques. Data collection techniques include observation, in-depth interviews, and documentation. Research results: personality and independence correctional counselling guidance with transactional communication went well. Child clients who initially had non-compliant behaviour in self-reporting and did not participate in personality and independence guidance activities experienced changes in compliance and recovered from psychological trauma. Transactional communication between pembimbing kemasyarakatan and child Clients uses the Didactic Method in an open manner, Empty Chairs can feel and understand the child Client's physical and psychological condition regarding their psychological trauma. Playing the role of mutual need between pembimbing kemasyarakatan and child clients. characterization The family trusts the child client, does not dictate to them, and always tries to provide examples of positive behavior to the child client. Analysis rituals of and leisure and awareness the willingness of pembimbing kemasyarakatan to place themsel with Klien anak. Analyze rituals and free time with awareness and the willingness of pembimbing pemasyarakatan to place themselves with child clients